Redesain Program Penguatan Satuan Pendidikan Anak Usia Dini Bernuansa Hindu Berbasis Keluarga di PAUD Kumara Asih Kota Mataram - Ni Made Arini; I Made Agus Yudhiarsana; Ida Bagus Alit Arta Wiguna (Cetta: Jurnal Ilmu Pendidikan, 2026)
Strengthening family-based early childhood education has become an important issue in early childhood education management because the quality of child development is influenced by institutional services and the continuity of parenting within the family. In Hindu-themed early childhood education (ECE), this need becomes even more important because the institution serves as a space for learning, character formation, and the strengthening of religious and cultural values. This research aims to analyse the implementation of the family-based early childhood education (ECE) strengthening programme at ECE Kumara Asih in Mataram City, identify the role of parents in its implementation, and formulate a more effective programme redesign. Using a qualitative approach with a case study design, data were collected through observation, interviews, documentation, and SWOT analysis. The research results show that five programme components, namely Parent Meeting Groups, Parental Involvement in Class, Parental Involvement in Joint Events, Consultation Days, and Home Visits, have been implemented, but their execution has not been optimal due to limitations in funding, human resources, space, and family participation time. The role of parents is stronger in collective activities, but it has not yet developed into an intensive pedagogical partnership. This research identifies a research gap related to the lack of institutional redesign that integrates all programme components adaptively and sustainably. The novelty of this research lies in the development of a family-based early childhood education management model that integrates local values and religious culture into the programme design.